2008
DOI: 10.1007/s00795-007-0372-9
|View full text |Cite
|
Sign up to set email alerts
|

Elastofibroma: a histochemical, immunohistochemical, and ultrastructural study of two patients

Abstract: Elastofibroma is a rare neoplasm. In this article, we report our study of the pathogenesis of fibrosis in elastofibroma. Three tumors obtained from two patients were selected. One patient was a 57-year-old Japanese woman who had a bilateral tumor, and the other patient was a 83-year-old Japanese man. All tumors occurred in the infrascapular region. Macroscopically, the cut surface of all tumors showed a poorly defined and whitish mass with yellowish foci. Microscopically, the tumor consisted of collagen fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…The cells are unanimously positive for vimentin [23][24][25][26][27], and most react for CD34 [23,[25][26][27][28] or bone sialoprotein [25]. Positive reaction for other antigens, such as promin-2, Cx43, Factor XIIIa, MEF-2 transcription factor [23,27], and TGF-b [28] has been reported in some studies. They are considered as fibroblasts [28] or consistent with the CD34 ?…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The cells are unanimously positive for vimentin [23][24][25][26][27], and most react for CD34 [23,[25][26][27][28] or bone sialoprotein [25]. Positive reaction for other antigens, such as promin-2, Cx43, Factor XIIIa, MEF-2 transcription factor [23,27], and TGF-b [28] has been reported in some studies. They are considered as fibroblasts [28] or consistent with the CD34 ?…”
Section: Discussionmentioning
confidence: 89%
“…Positive reaction for other antigens, such as promin-2, Cx43, Factor XIIIa, MEF-2 transcription factor [23,27], and TGF-b [28] has been reported in some studies. They are considered as fibroblasts [28] or consistent with the CD34 ? dendritic and fibroblast-like cells of the reticular dermis and fibrocollagenous soft tissues that are thought to act as potential mesenchymal stem cells [26].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The same investigators also could not find positivity with actin and desmin and reported that the previously described myofibroblastic differentiation was not seen in their lesions [6]. Similar to Hisaoka et al, there are other publications defining actin and desmin negativity in elastofibromas and reporting them to be of fibroblastic nature and not myofibroblastic [4,5,8,13].…”
Section: Discussionmentioning
confidence: 62%
“…The real etiology and pathogenetic mechanisms of elastofibromas are still controversial. There are only a few studies in the literature investigating the histochemical, immunohistochemical, and genetic features to determine the pathogenesis [8].…”
Section: Introductionmentioning
confidence: 99%